When Religious Beliefs Prohibit a Surgical Patient's Acceptance of Blood Transfusion. Issue 2 (April 2015) - Krishnamurthy, Kaarkuzhali B.
Abstract : ABSTRACT: A 49-year-old man who was a Jehovah's Witness presented with intractable epilepsy due to a brain tumor. The neurologist wanted to refer him for tumor resection but was concerned about requesting surgery for someone who would not accept blood products. The neurologist must balance his obligation of beneficence and nonmaleficence with respect for the patient's autonomous decision not to receive blood products. Good communication between patient and doctor is crucial to allow patients to make informed decisions about a choice to refuse transfusion, and doctors must accept the patient's autonomy, even when it conflicts with the moral imperative to provide treatment if it is available.